The Role of Organizational Leadership to Enhance Top 10 CSR Issues and Trends in The Global Economy - Rachmayanti, Dewi; Hubeis, Musa; Maarif, M. Syamsul; Affandi, M. Joko (Universitas Prasetiya Mulya, 2014)
Research on leadership and its relationship with organizational performance have been carried out and not considered CorporateSocial Responsibility (CSR) performance, especially in the field of community development (Comdev) and even done partially. This study aims to investigate the role of organizational leadership to enhance Top 10 CSR issues and trends in the global economy which defines roles and leadership competencies. Thirteen experts were involved in the Forum of Multi Stakeholder Corporate Social Responsibility (MSHCSR) through Focus Group Discussion (FGD). Data by cluster random sampling were statistically analyzed with Assumption Surfacing and Testing Strategy (SAST). The results showed from FGD experts stating if eight roles and eight competencies of the organization’s leadership is very important and influential to enhance Top 10 CSR issues and trends in the global economy.